Calabria - Cavallo, Maria Caterina; Cipriani, Filippo; Gerzeli, Simone; Demarteau, Nadia; Marocco, Alessia; Bamfi, Francesco (Farmeconomia. Health economics and therapeutic pathways, 2008)
In Calabria region 36,1% of women (aged 25-64) are screened regularly, meaning every 3 years. Considering regional tariffs and vaccine acquisition cost, the vaccination of 12-year-old girls with a 90% coverage could prevent 66 cases of cervicocarcinoma and 27 related deaths and thus results to be cost-effective (14.934 €/QALY). When the vaccination programme is extended to 16-year-old girls a further 72 cancer cases and 29 deaths could be prevented, with a very similar cost-effectiveness ratio. In Calabria region, the net cost for woman vaccinated is 175 € for the single cohort and 179 € for the multiple cohort.